INVESTASI SAHAM BAGI PEMULA - Siti Hanifa Sandri; Siti Samsiah; Misral Misral; Bakaruddin Bakaruddin; Sri Rahmayanti; Hendri Ali Ardi (LPPM UMRI, 2019)
Investing is the best option for maintaining financial security in the future. For most people especially beginners, investing is a very complicated thing and will make it confused to take the right investment decision. All types of investments contain elements of risk. Investor decisions are based on consideration of risk factors and expected gains. The purpose of this activity is to socialize the investment measures for beginners who are teachers and learners. Acquire the right knowledge of trends to buy stocks in the capital market for beginners i.e. teachers and students through live practice in the field. This method of community dedication uses lecture methods, direct demonstrations by the speaker, and questions and answers. The lecture method is used to convey knowledge on how to invest stocks for beginners. Demonstrations are used to provide direct examples of how to buy stocks on the capital markets. The result of this activity shows the participants very enthusiastic during the activities until the training is completed. Participants hope the next year can be given the opportunity to get similar training. Therefore, the investment will not be enough if done once. Keywords: Investing, stocks and beginners